Kurikulum cinta di MTSN Kota Batu: Analisis kurikulum islam dan implementasinya - hidayat, sahrul haj; F, Hilda Amelia; Nadia, Sakila Ainun (Maliki Interdisciplinary Journal, 2025)
The concept of intelligence in Islam and its relationship to the development of an intelligent Islamic education curriculum. Intelligence in Islam is understood as a gift from Allah SWT that distinguishes humans from other creatures, enabling them to think, learn, and develop their potential. The Qur’an and Hadith emphasize that intelligence must be used positively, through self-control and preparation for the afterlife. This study aims to describe the implementation of the Love-Based Curriculum (KBC) at MTsN Batu as a form of curriculum that fosters intelligence from an Islamic perspective. This curriculum emphasizes the development of love for Allah, the Prophet, fellow human beings, and the environment as the main foundation for character formation of students. The study used qualitative methods with data collection techniques through observation and interviews with teachers, students, and madrasah officials. The results showed that the implementation of the KBC at MTsN Batu was carried out in stages through adjustments to learning tools, religious habituation activities, and teacher training to strengthen pedagogical and spiritual competencies. Learning practices were not only oriented towards academic achievement, but also on the development of students’ moral and spiritual values. Furthermore, routine activities at Mtsn Batu are an integral part of fostering a religious and character-based learning environment. The Love-Based Curriculum at MTsN Batu creates a balanced Islamic education model that promotes intellectual, spiritual, and moral development.